Urbanization and Child Nutritional Outcomes - Amare, Mulubrhan; Arndt, Channing; Abay, Kibrom A.; Benson, Todd (Published by Oxford University Press on behalf of the World Bank, 2021)
The implications of urbanization on child nutritional outcomes are investigated using satellite-based nighttime light intensity data as a marker of urbanization with data from two rounds of the Nigeria Demographic and Health Survey. Nighttime light introduces a gradient of urbanization permitting investigation of the implications of urbanization on child nutritional outcomes along an urbanization continuum. Nightlight is found to significantly predict child nutritional outcomes even after controlling for observable covariates known to influence child nutrition. In all specifications, improvements in child nutrition outcomes onset with relatively low levels of light emissions and continue rapidly as nightlight intensity increases before largely leveling off. These nonlinear relationships highlight the value of nightlight as a population agglomeration indicator relative to traditional binary rural-urban indicators. Consistent with other recent work, patterns of urbanization influence welfare outcomes. At least for Nigeria, a pattern that extends the benefits of urban agglomeration to larger shares of the population would speed improvements to child nutritional outcomes.